2022
DOI: 10.3390/ijerph19159265
|View full text |Cite
|
Sign up to set email alerts
|

Needs of Lung Cancer Patients Receiving Immunotherapy and Acceptance of Digital and Sensor-Based Scenarios for Monitoring Symptoms at Home—A Qualitative-Explorative Study

Abstract: Background: The development of immunotherapy in the treatment for lung cancer has changed the outlook for both patients and health care practitioners. However, reporting and management of side effects are crucial to ensure effectiveness and safety of treatment. The aim of this study was to learn about the subjective experiences of patients with lung cancer receiving immunotherapy and to explore their potential acceptance of digital and sensor-based systems for monitoring treatment-related symptoms at home. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(67 reference statements)
0
2
0
Order By: Relevance
“… 42 , 45 Accordingly, Kutzleben et al. 46 demonstrated that involving caregivers was extremely helpful. Similarly, taking enough time is fundamental.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 , 45 Accordingly, Kutzleben et al. 46 demonstrated that involving caregivers was extremely helpful. Similarly, taking enough time is fundamental.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients could be provided with summaries of information and enough time to paraphrase what was explained, reviewing information again with the physician. 42,45 Accordingly, Kutzleben et al 46 demonstrated that involving caregivers was extremely helpful. Similarly, taking enough time is fundamental.…”
Section: Discussionmentioning
confidence: 99%